Identification and phylogenetic analysis of the complete mitochondrial genome of Mediterranean buffalo (Artiodactyla: Bovidae) - Lin, Qian (Mitochondrial DNA B Resour, 2020)
Mediterranean buffalo (Bubalus bubalis Linnaeus, 1758 breed Mediterranean, MEB) is one of the best milk-producing breeds in river-type buffaloes in the world. It is the first time that the complete mitochondrial genome sequence of the MEB was reported. The total length of the mtDNA is 16,357 bp, It contains the typical structure, including 22 transfer RNA genes, 2 ribosomal RNA genes, 13 protein-coding genes and 1 non-coding control region (D-loop region). The overall composition of the mtDNA was estimated to be 33.10% for A, 26.44% for T, 26.57% for C and 13.89% for G, in the order A > C > T > G feature occurs in the MEB. Phylogenetic analyses using N-J computational algorithms showed that the analyzed 18 ruminantia species are divided into four major clades: Bovidae, Cervidae, Giraffidae and Atilocapridae. In addition, our work confirmed that MEB and Nili-Ravi buffalo (NRB) have a close genetic relationship with fellow tribal members Murrah buffalo. Meanwhile, we also found that MEB and NRB have highly similar genetic relationship.